2001
DOI: 10.1152/jappl.2001.90.4.1407
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-enhanced satellite cell proliferation and new myonuclear accretion in rat skeletal muscle

Abstract: The effects of increased functional loading on early cellular regenerative events after exercise-induced injury in adult skeletal muscle were examined with the use of in vivo labeling of replicating myofiber nuclei and immunocyto- and histochemical techniques. Satellite cell proliferation in the soleus (Sol) of nonexercised rats (0.4 +/- 0.2% of fibers) was unchanged after an initial bout of declined treadmill exercise but was elevated after two (1.0 +/- 0.2%, P < or = 0.01), but not four or seven, daily bouts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
96
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(105 citation statements)
references
References 36 publications
9
96
0
Order By: Relevance
“…22 Hybrid myotubes formed in vitro by the fusion of normal rat and dystrophic mdx mouse myoblasts showed that dystrophin was present over the entire membrane of all hybrid myotubes even when nuclei ratio normal/dystrophic was low (as low as 1 of 12). 22 In vivo transplantation of normal myoblasts into mdx mouse muscle 23 in which myogenic cells fuse with pre-existing fibers, showed that the dystrophin nuclear domain is ϳ300 to 400 m. 24,25 These results are very similar to those we observed after BM transplantation (116 m). In a previous study using direct myoblast injection in mdx muscle, the dystrophin domain was shown to be twofold to threefold smaller than that of soluble cytoplasmic ␤-galactosidase used as a reporter gene.…”
Section: Discussionsupporting
confidence: 55%
“…22 Hybrid myotubes formed in vitro by the fusion of normal rat and dystrophic mdx mouse myoblasts showed that dystrophin was present over the entire membrane of all hybrid myotubes even when nuclei ratio normal/dystrophic was low (as low as 1 of 12). 22 In vivo transplantation of normal myoblasts into mdx mouse muscle 23 in which myogenic cells fuse with pre-existing fibers, showed that the dystrophin nuclear domain is ϳ300 to 400 m. 24,25 These results are very similar to those we observed after BM transplantation (116 m). In a previous study using direct myoblast injection in mdx muscle, the dystrophin domain was shown to be twofold to threefold smaller than that of soluble cytoplasmic ␤-galactosidase used as a reporter gene.…”
Section: Discussionsupporting
confidence: 55%
“…Sections were counterstained with hemalaun and examined by light microscopy (Axioskop 40, Zeiss, Göttingen, Germany). By labeling of laminin, which is present in the basement membrane, confirmation of proliferating satellite cells was able through their localization beneath the laminin-positive basal lamina in the survival zone, as described by Smith et al 19 in the soleus muscle of rats. The fact that the penumbra areas still revealed myocytes allowed us to identify proliferating satellite cells due to their localization beneath their basal lamina.…”
Section: Histochemistry and Immunohistochemistrymentioning
confidence: 61%
“…Satellite cells are a small population of myogenic progenitors that reside between the sarcolemma and basal lamina of the muscle fiber, and they play a crucial role in postnatal muscle growth and regeneration (reviewed in Zammit et al, 2006). Following skeletal muscle injury or exercise-induced activation, the normally quiescent Pax7-expressing satellite cells proliferate extensively and up-regulate expression of MyoD (Smith et al, 2001;Yan et al, 2003;Montarras et al, 2005) and Myf-5 (Conboy and Rando, 2002;Yan et al, 2003), before differentiation into skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%
“…Satellite cells are a small population of myogenic progenitors that reside between the sarcolemma and basal lamina of the muscle fiber, and they play a crucial role in postnatal muscle growth and regeneration (reviewed in Zammit et al, 2006). Following skeletal muscle injury or exercise-induced activation, the normally quiescent Pax7-expressing satellite cells proliferate extensively and up-regulate expression of MyoD (Smith et al, 2001;Yan et al, 2003;Montarras et al, 2005) and Myf-5 (Conboy and Rando, 2002;Yan et al, 2003), before differentiation into skeletal muscle.Pax3 and Pax7 are members of the Pax transcription factor family and contain both paired (PD) and homeodomain (HD) DNA binding motifs. Pax3 and Pax7 can bind to DNA sequences containing either a consensus paired domain binding site (GTCAC A/G C/G A/T T/C) or a homeodomain binding site (ATTA) (Chalepakis et al, 1994;Chalepakis and Gruss, 1995).…”
mentioning
confidence: 99%